Nilai-Nilai Moderasi Beragama dan Implementasinya Dalam Pendidikan Agama Islam di Abad 21 - Acep Saefuddin; Cecep Sumarna; Abdul Rozak (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article aims to discuss the values ​​of religious moderation and their implementation in Islamic religious education in the 21st century. This research uses a qualitative method with a descriptive approach. Data analysis is more focused on library research or literature studies. The conclusion in this study is that the 21st century is marked by the emergence of an era of disruption, due to the great influence of technology in this century, changing trends, namely from analog trends to digital trends with digital innovations that make everything easy. So to face this era, special skills are needed including critical thinking, creativity, communication, and collaboration. Religious moderation is a religious attitude with the principle of balance and fairness so that it will avoid excessive attitudes. The implementation of religious moderation values ​​in PAI learning is one of the solutions in facing the challenges of this century and in order to ward off radical attitudes in religion which is also one of the influences social media. PAI learning has a strategic role in achieving the goals of National Education, especially those related to instilling faith and devotion to God Almighty and increasing noble character